Currículo e integração curricular em um curso de graduação em medicina: concepções manifestadas pelos docentes que o vivenciam - Rodrigues, Aline de Fatima Cruz (2018)
The present research aims to describe and analyze the relationship between the proposal of integrated curriculum of the undergraduate course in Medicine, Federal University of São Carlos (UFSCar) and the conceptions manifested by its teachers on curriculum and curricular integration. For this, the study of the Pedagogical Project of this course was carried out, with emphasis on its reference framework and its structural framework. The research was carried out by means of interviews with 11 teachers who work in the course, being chosen based on predetermined criteria. These criteria took into account the duration of the course and the activity / cycle in which they acted in the course and were determined based on the hypotheses that: a) the teachers who acted in the course from the beginning would have conceptions more coherent with what is proposed in the PPC than the newcomers; b) there would be a difference between the conceptions of teachers who work in the different educational cycles of the course. After the interviews, the data were transcribed literally and then organized, tabulated and analyzed in the light of the theoretical framework used. It was possible, through this research, to analyze the type of curricular integration proposed in the mentioned pedagogical project of course and to describe the conceptions of curriculum and curricular integration manifested by its teachers. As results, we find conceptions of curricular integration that approximate what is foreseen in the PPC of the course, but according to the participants of the research, this integration is not effective as is foreseen in the PPC. It was also possible to verify that all the interviewees participated in training activities when they entered the course, and that most of the teachers interviewed conceive the curriculum only in its formal dimension, that is, as an official document. It was also possible to verify that the participants of the research did not oppose what is included in the Pedagogical Project of the course, but affirm that this project needs to be revisited and reformulated based on its more than ten years of operation, stating what has been successful and adapting what is not in accordance with the provisions of the PPC. Finally, the hypotheses presented were not confirmed, since all 11 teachers interviewed presented conceptions of curricular integration very close to what is presented in the PPC of the course, regardless of the activity / cycle in which they work and the year of admission as a teacher.